2014
DOI: 10.3109/02699052.2014.910702
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative computer tomography analysis of post-operative subdural fluid volume predicts recurrence of chronic subdural haematoma

Abstract: Close imaging follow-up is important for CSDH patients for recurrence prediction. Using quantitative CT volumetric analysis, strong evidence was provided that changes in the residual fluid volume during the 'self-resolution' period can be used as significantly radiological predictors of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…volume than bilateral SDH in a separate patient (14). Similarly, Xu et al (15) showed that bilateral cSDH were not associated with recurrence; however, with 44 bilateral cases and 10 unilateral cases, the number of patients in that study was small. In contrast, Shen et al (16), reviewed 102 patients where bilateral cSDH was an independent risk factor for recurrence.…”
Section: Discussionmentioning
confidence: 83%
“…volume than bilateral SDH in a separate patient (14). Similarly, Xu et al (15) showed that bilateral cSDH were not associated with recurrence; however, with 44 bilateral cases and 10 unilateral cases, the number of patients in that study was small. In contrast, Shen et al (16), reviewed 102 patients where bilateral cSDH was an independent risk factor for recurrence.…”
Section: Discussionmentioning
confidence: 83%
“… 16 Therefore, it was not surprising when recent studies, through more sophisticated quantitative volumetric analyses of CT scans in patients with CSDH, demonstrated that a large V 1 and large V 2 , regardless of whether the lesions were unilateral or bilateral, may be predictors of recurrence. 6 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, semiautomatic quantitative radiological analysis is a valid predictor of functional outcomes in other neurological conditions like aneurysmal subarachnoid hemorrhage or traumatic brain injury 23,36,37 . Additionally, prior studies have shown the relevance of using these accurate quantitative methods to optimize the surgical evacuation of CSDH 13‐17,38 …”
Section: Discussionmentioning
confidence: 99%
“…Instead, accurate prediction of postoperative outcomes warrants a multidisciplinary approach weighing radiographic, etiologic, and management‐related factors. Although quantitative volumetric and texture analyses of computed tomography (CT) images have been previously used to predict the risk of recurrence in CSDH, 13‐17 there are limited data correlating this approach to functional outcome. Therefore, the objective of this study was to determine whether preoperative CT could serve as an objective and accurate complementary test for prognostication of short‐term postoperative outcomes for patients with CSDH.…”
Section: Introductionmentioning
confidence: 99%